Functions of Computerized Accountancy - Chluska, J. (Электронное моделирование, 2008)
The information created within accountancy system is more and more frequently used in company’s management and the computerized accountancy is expected to provide information not only retrospective by also prospective one. This paper presents functions of computerized accountancy related to informational expectations of information recipients.